(NwAKUUMNYE KWANTOWYE \FFEKTY W SILXNYH POLQH (B/s - (NgRIB(B, (NaNDREJ aNATOLXEWI^s; (NmAMAEW(B, (Ns(B.(Ng(B.s; (NmOSTEPANENKO(B, (Nw(B.(Nm(B.s ((NmOSKWA (B:s (N|NERGOATOMIZDAT(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 276-283 (291 (NNAZW(B.)s
(NaLF(B.-(NPREDM(B. (NUKAZ(B.: (NS(B. 284-285s
(NzAGL(B. 1-(NGO IZD(B.: (NkWANTOWYE \FFEKTY W INTENSIWNYH WNE[NIH POLQHs
Keywords: (NkWANTOWAQ TEORIQ POLEJs